Bioprospecção de extratos de macroalgas marinhas bentônicas do litoral de Alagoas - Guedes, Élica Amara Cecília (2011)
Compounds present in marine algae can play important biological functions, such as: antimicrobial activity, antifungal, cytotoxicity, larvicidal, molluscicidal, direct “in vivo” or indirectly, activating the defense mechanisms of the hosts. The objective of this study was to evaluate the biological activity of marine benthic algae extracts collected from a beach located on the north coast of Alagoas called Praia de Riacho Doce. Extracts and fractions obtained from algae: Dictyota dichotoma, Padina gymnospora, Digenea simplex, Hypnea musciformis, Sargassum vulgare, Ulva lactuca, Gracilaria caudata, Galaxaura rugosa and Gellidium pusillum were all tested. After collecting, sorting and identifying the dried and powdered seaweed (500g), they were submitted to an extraction with solvents: dichloromethane, chloroform, methanol, ethanol and water. The dichloromethane extracts of H. musciformis and P. gymnospora were selected for fractioning because they presented better yielding. A cytotoxicity evaluation was done facing the human cancerous cells: NCI-H292 - human lung cancer, HEp-2 - epidermoide carcinoma of human larynx, K562 - chronic myelocytic leukemia; facing the dermatophytic fungi: Trichophyton rubrum, T. tonsurans, T. mentagrophytes, Microsporum canis, M. gypseum, Epidermophyton flocossum - and four species of Candida (C. albicans, C. krusei, C. guilliermondii, C. parapsilosis) as well as the evaluation of larvicidal activity against Aedes aegipty, molluscicidal against Biomphalaria glabrata and toxic against Artemia salina. The cytotoxicity activity was done by colorimetric MTT-Methyl Tetrazolium Triazole according to the National Cancer Institute (NCI) protocol. For the fungicidal activity, the methodology outlined in document M27-A2 and M38A was used by the Clinical and Laboratory Standard Institute appropriate for dermatophytes and by M44A standards for Candida. In the bioassays for the control of Aedes aegipty, larvae from the fourth instar in two repetitions were used and extracts that had a mortality rate of less than 50% followed for the tests found. Toxicity assay against brine shrimp nauplii were performed according to the methodology given in literature with some modifications, to obtain mean lethal concentrations (LC50). We note that extracts with higher anticancer action are from species H.musciformis, D. simplex, P. gymnospora, S. vulgare, D. dichotoma, particularly the extracts dichloromethane, chloroform and chloroform fraction. The test results with A. saline showed a low toxicity of the crude extracts of marine algae tested, since, except the ethanolic extract of H. musciformis, all extracts showed LC50> 10-3. Regarding B. glabrata, only the chloroform fractions of the species H. musciformis and P. gymnospora showed molluscicidal activity. Regarding dermatophytes and Candida, dichloromethane and ethanol extracts were the best that have antifungal activity. The results showed that the algae from the coast of Alagoas have a potential that this was not explored until allowing a very promising future use.